PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER, NET PROFIT MARGIN DAN UKURAN PERUSAHAAN TERHADAP PERTUMBUHAN LABA - Untung Sriwidodo, Mita Febriana Puspasari, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The purpose of this study was to analyze the significance effect ofcurrent ratio, debt to equity ratio, total asset turnover, net profit margin andsize of the company profit growth. This type of research is empirical researchin the pharmaceutical sub-sector manufacturing companies listed inIndonesia Stock Exchange 2011-2015. A sample of 8 companies with totalsampling technique. Data collection technique used documentation.Mechanical analysis using multiple linear regression analysis. The resultsshowed that the current ratio of no significant effect on earnings growth. Debtto equity ratio significant effect on earnings growth. Total asset turnover havea significant effect on earnings growth. Net profit margin significant effect onearnings growth. Company size significantly influence the profit growthKeywords: current ratio, debt to equity ratio, total asset turnover, net profitmargin, firm size, profit growth.